Mensch &Amp; Computer Interaktion 2007 2007
DOI: 10.1524/9783486845488-010
|View full text |Cite
|
Sign up to set email alerts
|

Laserpointer-Interaktion für große, hochauflösende Displays

Abstract: ZusammenfassungAufgrund des limitierten Sehvermögens des Menschen muss sich ein Anwender vor großen, hochauflö-senden Displays frei bewegen können, um kleinste Details pixelgenau wahr zu nehmen oder einen Überblick über die gesamte Darstellungsfläche von mehreren Quadratmetern zu erhalten. Im Gegensatz zu konventionellen Eingabegeräten wie Maus und Tastatur beschränken Laserpointer den Anwender nicht in seiner Bewegungsfreiheit, sondern ermöglichen unabhängig von der Position zum Display eine sehr intuitive un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…To increase pointing accuracy, jitter reduction is a requirement. König et al [113] showed that an infrared laser pointer can be successfully employed to create a virtual cursor that can be stabilized using prediction filtering algorithms. An operator was switching between the application-states in our prototype.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To increase pointing accuracy, jitter reduction is a requirement. König et al [113] showed that an infrared laser pointer can be successfully employed to create a virtual cursor that can be stabilized using prediction filtering algorithms. An operator was switching between the application-states in our prototype.…”
Section: Discussionmentioning
confidence: 99%
“…External tracking via computer vision solutions is described in Section 2.4.3 and via (absolute) position sensors in Section 2.4.4. Internal tracking is done in the popular Nintendo Wiimote by detecting fixed infrared light sources with an on-board camera, see Figure 2.4b, or by using a laser pointer that projects onto a surface [113]. Relative position sensors are also applied in handheld devices.…”
Section: Handheld Devicesmentioning
confidence: 99%
See 3 more Smart Citations